A common co-morbidity modulates disease expression and treatment efficacy in inherited cardiac sodium channelopathy. (27th April 2018) - Rivaud, Mathilde R; Jansen, John A; Postema, Pieter G; Nannenberg, Eline A; Mizusawa, Yuka; van der Nagel, Roel; Wolswinkel, Rianne; van der Made, Ingeborg; Marchal, Gerard A; Rajamani, Sridharan; Belardinelli, Luiz; van Tintelen, J Peter; et al.
Abstract: Aims: Management of patients with inherited cardiac ion channelopathy is hindered by variability in disease severity and sudden cardiac death (SCD) risk. Here, we investigated the modulatory role of hypertrophy on arrhythmia and SCD risk in sodium channelopathy. Methods and results: Follow-up data was collected from 164 individuals positive for the SCN5A -1795insD founder mutation and 247 mutation-negative relatives. A total of 38 (obligate) mutation-positive patients died suddenly or suffered life-threatening ventricular arrhythmia. Of these, 18 were aged >40 years, a high proportion of which had a clinical diagnosis of hypertension and/or cardiac hypertrophy. While pacemaker implantation was highly protective in preventing bradycardia-related SCD in young mutation-positive patients, seven of them aged >40 experienced life-threatening arrhythmic events despite pacemaker treatment. Of these, six had a diagnosis of hypertension/hypertrophy, pointing to a modulatory role of this co-morbidity. Induction of hypertrophy in adult mice carrying the homologous mutation ( Scn5a 1798insD/+ ) caused SCD and excessive conduction disturbances, confirming a modulatory effect of hypertrophy in the setting of the mutation. The deleterious effects of the interaction between hypertrophy and the mutation were prevented by genetically impairing the pro-hypertrophic response and by pharmacological inhibition of the enhanced late sodium current associated with the mutation. Conclusion: This study provides the first evidence for a modulatory effect of co-existing cardiac hypertrophy on arrhythmia risk and treatment efficacy in inherited sodium channelopathy. Our findings emphasize the need for continued assessment and rigorous treatment of this co-morbidity in SCN5A mutation-positive individuals.